1995
DOI: 10.1016/0169-5150(95)01143-9
|View full text |Cite
|
Sign up to set email alerts
|

Sources of agricultural productivity growth and stagnation in sub-Saharan Africa

Abstract: This paper examines sources of agricultural growth in sub-Saharan Africa. Growth in the stock of traditional inputs (land, labor, livestock) remains the dominant source of output growth. Growth in modern input use was of secondary importance, but still accounted for a 0.2-0.4% annual growth rate in three of four sub-regions.Econometric results support earlier studies that suggest that land abundance may be a constraint on land productivity growth. Growth in agricultural exports and historic calorie availabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
3
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 30 publications
3
17
3
2
Order By: Relevance
“…A 1% increase in farm size would decrease output by 0.29 %. These findings are in line with Frisvold and Ingram (1994) who found that for small fields the production is normally small, but in terms of productivity or production per hectare they perform better than larger plots.…”
Section: Research In Applied Economicssupporting
confidence: 81%
“…A 1% increase in farm size would decrease output by 0.29 %. These findings are in line with Frisvold and Ingram (1994) who found that for small fields the production is normally small, but in terms of productivity or production per hectare they perform better than larger plots.…”
Section: Research In Applied Economicssupporting
confidence: 81%
“…However, these findings are contrary to the ones of some newer studies applying more sophisticated econometric methods which either did not include education variables at all in the model (e.g. Frisvold and Ingram 1995), or found insignificant (Vollrath 2007) or even puzzling negative coefficients for the education variables used (Craig et al 1997). Hence, the literature so far can be judged as rather inconclusive about the role of education for agricultural productivity in the international context.…”
Section: Introductioncontrasting
confidence: 54%
“…The implication is that any increase in the farm size would reduce the returns to be realized from the sales of mushrooms, so an extra cost in inputs does not translate into better returns. These findings are similar to those of Frisvold and Ingram (1994) who found that for small fields the production is normally small, but in terms of productivity they perform better than larger plots. Notes: ** = significant at 1% level, *=significant at 5% level It is evident from the study that the estimates for lambda and sigma squared in the study area ISSN 2327-0640 2018 are 0.0123 and 0.1508 respectively and lambda is statistically significant at 1%, indicating a good fitness and correctness of the specified distribution assumption.…”
Section: Technical Efficiency Of Mushroom Farmerssupporting
confidence: 81%